1969
DOI: 10.1063/1.1657182
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin Scattering Near the Glass Transition of Polymethyl Methacrylate

Abstract: Local acoustoelasticity in poly(methyl methacrylate) by Brillouin scattering J. Appl. Phys. 54, 5456 (1983); 10.1063/1.332729 Brillouin scattering near the lowtemperature glass transitions of polymethyl methacrylate Brillouin scattering of laser light has been used to measure the frequency of hypersonic sound waves in the range of 10 10 Hz in PMMA as a function of temperature through the glass-transition region. A discontinuity in the temperature coefficient of sound velocity is observed at the glass-transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In the eigenmode spectra shown in Figure a,c, the first few strongest eigenmodes can be easily resolved by Lorentzian-shaped fitting curves; each mode is characterized by its frequency position f R and line width Γ. The variation with temperature of these two quantities, f R ( T ) and Γ­( T ), depicted in Figures b and d, is of importance to deduce the glass transition. …”
Section: Resultsmentioning
confidence: 98%
“…In the eigenmode spectra shown in Figure a,c, the first few strongest eigenmodes can be easily resolved by Lorentzian-shaped fitting curves; each mode is characterized by its frequency position f R and line width Γ. The variation with temperature of these two quantities, f R ( T ) and Γ­( T ), depicted in Figures b and d, is of importance to deduce the glass transition. …”
Section: Resultsmentioning
confidence: 98%
“…Thus the features of the D as a function of temperature are essentially reflecting the corresponding changes in the sound velocity. The results of numerous experimental investigations 40 carried out at low and high frequencies have shown that the sound velocity in polymers depends linearly on temperature and that only at those points where the mode of molecular motion is changed does the temperature coefficient of the sound velocity change discontinuously. Thus the unfreezing of one or another type of molecular motion can be accessed from the kink in the temperature dependence of the sound velocity.…”
Section: D ͑2͒mentioning
confidence: 99%
“…44 This allows for high temporal sampling of the Brillouin shift while sweeping the temperature of the sample in time. A sudden change in the slope of this curve is indicative of the temperature of the glass transition, 45 which can be easily calculated from temperature-dependent measurements of the Brillouin shift. Thus, while early studies have shown that such methods are technically feasible, improved instrumentation which is both robust and simple may lead to widespread adoption of Brillouin scattering as a glass transition metric.…”
mentioning
confidence: 99%
“…For this reason, previous studies utilizing Brillouin light to examine polymers were limited to carefully prepared samples with extremely fine optical smoothness and near-ideal transparency. 45 In this study, we utilize a Rubidium atomic vapor notch filter with a narrow D 2 absorption line at 780.24 nm in vacuum. The source laser is then electronically locked to the D 2 transition of Rubidium so that the output wavelength and thus the elastically scattered light are strongly absorbed by the Rb vapor, with extinction exceeding À100 dB over a narrow ($500 MHz) bandwidth.…”
mentioning
confidence: 99%